Civil Aviation in the Netherlands East Indies during the Great Depression, 1928-1934 - Untarawati, Dewik; Tangkulisan, Yuda Benharry (International Journal of Engineering and Technology, 2018)
The beginning of civil aviation in the Netherlands East Indies was started by the creation of Koninklijke Netherlandsch Indische Luchtvaart Maatschappij (KNILM) or the Royal East Indies Airways in November 1st, 1928. As the only airline which held a monopoly to run air services in the Netherlands East Indies, KNILM had no competitor. One year after the establishment of the airline, the Great Depression occurred and caused a setback in many sectors of economy in the World and the Netherlands East Indies as well. This paper offers an overview of the creation and early growth of civil aviation in the Netherlands East Indies, and outlines some implications of the air transport in the colony during the Great Depression. The paper will be written in historical perspective by using some primary sources from the collection of the National Library of Republic IndonesiaÂ and Universiteits Bibliotheek Leiden (UBL), supplemented by magazines, newspaper, maps, and books. Luchtvaart and KNILM Nieuws were two magazines which become the official organs of KNILM and given a unique perspective into the operation of civil aviation in the Netherlands East Indies from 1928 to 1934,Â